Standard fire resistance tests for wire cloths sprayed with intumescent fireproof coating. (April 2013) - Mo, H.-C.; Hung, M.-F.; Kuo, S.-Y.; Lin, P.-J.; Tang, C.-H.; Chuang, Y.-J.; Lin, C.-Y.
Abstract : In this study, an experiment was performed on the fire exposed area (1×1 m) of a standard wall furnace; a radiometer, thermocouple and theoretical analysis were used to examine the fire behaviour of wire cloths sprayed with an intumescent fireproof coating. The experimental results showed that using wire cloths sprayed with intumescent fireproof coatings achieves a 1 h fire integrity rating for fire prevention and reduces the radiant heat of the fire resistance. The results proved that spraying an intumescent fireproof coating on wire cloths is a feasible fireproofing technique that can be applied to buildings.